Surfactant therapy for acute respiratory distress in children - Moretti, C.; Papoff, P.; Barbàra, et al., C.S. (Acta Biomedica Atenei Parmensis, 2013)
In children with acute lung injury the endogenous surfactant system is altered via a variety of different mechanisms, including inflammation, vascular dysfunction, oxidant injury, cellular injury and oedema. This article examines the pathophysiology of acute lung injury and surfactant use for treatment of acute respiratory failure in infants and children.